2016
DOI: 10.1016/j.soilbio.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of elevated CO2 on carbon and nitrogen functional capacity of microbial communities in three contrasting soils

Abstract: Elevated atmospheric CO 2 (eCO 2) affects soil-plant systems by stimulating plant growth, rhizosphere processes and altering the amount and quality of organic matter inputs. This study examined whether these plant-mediated processes indirectly influence the structure and function of soil microbial communities and soil carbon (C) and nitrogen (N) cycling. Surface soils (0-5 and 5-10 cm) of Calcarosol, Chromosol and Vertosol were sampled after 5 years' exposure to either ambient CO 2 (aCO 2 ; 390 ppm) or eCO 2 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 91 publications
3
29
0
Order By: Relevance
“…Previous studies have reported that elevated CO 2 or N addition increased, decreased, or had no significant impact on community structure 7, 15, 16, 26, 28, 52 . These contradictory results could be due to differences of microbial substrate availability under different scenarios of climate change.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported that elevated CO 2 or N addition increased, decreased, or had no significant impact on community structure 7, 15, 16, 26, 28, 52 . These contradictory results could be due to differences of microbial substrate availability under different scenarios of climate change.…”
Section: Discussionmentioning
confidence: 89%
“…Soils were air dried overnight and sieved to remove particles larger than 2 mm. A single soil sample was generated for each site by pooling all four collected soils from the subsite plots (Aye et al, 2016, Butterly et al, 2016). The collected stock soils were separately stored at ambient room temperature (21°C) in airtight plastic containers for four months, followed by subsampling (representing the first sampling timepoint; labelled as ‘T0’ in the analysis) for immediate treatments as described below.…”
Section: Methodsmentioning
confidence: 99%
“…Singletons and low abundance amplicons (<1% relative abundance) were disregarded (Fisher and Triplett, 1999). Data were normalized in the statistical software R version 3.3.2 (The R Foundation for Statistical Computing, Boston, USA), with bin sizes of 3 and 4 selected for bacteria and fungi respectively (Ramette, 2009, Butterly et al, 2016). The following analyses were conducted in Primer-E v6 (Quest Research Ltd., Auckland, New Zealand), with treatments considered as fixed factors and microbial responses analysed for each soil separately (Chow et al, 2013, Wood et al, 2016): 1) Bray-Curtis similarity for microbial communities; 2) SIMPER analysis to identify the contribution of individual Operational Taxonomic Units (OTUs) to (dis)similarity between replicates or different treatments; 3) DIVERSE to determine Shannon diversity index (H’) for sample data; 4) Permutational multivariate analysis of variance (PERMANOVA) to determine treatment effect (melatonin, stressors: cadmium and Salt) on microbial assemblages for each soil at various concentrations (High, Low and Zero).…”
Section: Methodsmentioning
confidence: 99%
“…These effects may alter the activity and composition of the rhizosphere inhabiting microbial community which in turn can greatly affect plant growth and health (Rogers, Runion, & Krupa, ). Recent studies investigating the effect of elevated [CO 2 ] on the soil or root‐associated prokaryotic diversity or community composition however, reported contradictory results showing either significant (Deng et al., ; He et al., ; Gschwendtner et al., ; Okubo et al., ) or no effects (Butterly et al., ; Hayden et al., ; Ren et al., ). It seems that the response of the soil prokaryotic community is characteristic to ecosystems and plant species (Dunbar et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies investigating the effect of increased [CO 2 ] on the composition of the soil microbial community relied on methods with relatively low resolution, like 16S rRNA gene clone libraries (Dunbar et al., ), fingerprinting techniques (Butterly et al., ; Gschwendtner et al., ), PhyloChip (Hayden et al., ; He et al., ), and 454 pyrosequencing of 16S rRNA gene amplicons with shallow sequencing depths (Deng et al., (1698–3299 sequences/sample); Ren et al., (2,000 sequences/sample); Okubo et al., (2523–14395 sequences/sample)). However, considering that rare taxa may be more responsive to climate factors, methods with higher resolutions should be applied (Dunbar et al., ).…”
Section: Introductionmentioning
confidence: 99%